Homogenized lattice Boltzmann model for simulating multi-phase flows in heterogeneous porous media. (December 2022) - Lautenschlaeger, Martin P.; Weinmiller, Julius; Kellers, Benjamin; Danner, Timo; Latz, Arnulf
Abstract: A homogenization approach for the simulation of multi-phase flows in heterogeneous porous media is presented. It is based on the lattice Boltzmann method and combines the grayscale with the multi-component Shan–Chen method. Thus, it mimics fluid–fluid and solid–fluid interactions also within pores that are smaller than the numerical discretization. The model is successfully tested for a broad variety of single- and two-phase flow problems. Additionally, its application to multi-scale and multi-phase flow problems in porous media is demonstrated using the electrolyte filling process of realistic 3D lithium-ion battery electrode microstructures as an example. The approach presented here shows advantages over comparable methods from literature. The interfacial tension and wetting conditions are independent and not affected by the homogenization. Moreover, all physical properties studied here are continuous even across interfaces of porous media. The method is consistent with the original multi-component Shan–Chen method (MCSC). It is as stable as the MCSC, easy to implement, and can be applied to many research fields, especially where multi-phase fluid flow occurs in heterogeneous and multi-scale porous media. Highlights: Approach for simulating flow of immiscible components in heterogeneous porous media. Consistent coupling of grayscale method and multi-component Shan–Chen method. Extensive validation for single- and two-phase flow phenomena in porous media. Contact angle and interfacial tension not affected by homogenization. Broad applicability demonstrated for filling of lithium-ion battery microstructures.